Effect of the Acid Degradation of the Shinan Shipwreck on Indoor Air Quality in the Korean National Maritime Museum. (4th July 2021) - Kim, Seojin; Kim, Eung-ho; Lee, Yu-na
ABSTRACT : Archaeological wet wood undergoes acid degradation in an uncontrolled exhibition environment if the iron compounds are not completely removed prior to its preservation treatment with polyethylene glycol (PEG). However, completely removing such compounds that have deeply penetrated the wood tissue and fully control the exhibition environment are difficult. The Shinan shipwreck – on display at the Korean National Maritime Museum – is experiencing acid degradation, which in turn is affecting the surrounding air quality. This study investigated the effect of acid degradation on air quality of the exhibition gallery; the temperature, humidity, volatile organic compounds, aldehydes, nitrogen dioxide, and sulfur dioxide were monitored from April 2018 to March 2019. An analysis of the data revealed that the formaldehyde and sulfur dioxide concentrations in the exhibition hall were extremely high during the summer, which was largely attributed to the acid degradation of the shipwreck. Therefore, continuously operating a heating, ventilation, and air conditioning (HVAC) system and maintaining the temperature in the gallery below 24°C are required for safe conservation of the artefacts in the gallery.